PENGARUH REWARD AND PUNISHMENT TERHADAP DISIPLIN KERJA KARYAWAN PADA PT FAJAR BARU SUKSES KABANJAHE - Menanti Sembiring; Ingan Ukur Sitepu; Putri Yulianti Hutasoit (Universitas Quality, 2021)
This research is conducted with the aim to know the influence of reward and punishment to employee work discipline to the PT Fajar Baru Sukses Kabanjahe. The sample in this research were 35 respondents. Techniques of data collection was done by filing questionnaires to respondents. The research method to analyze the data using quantitative methods, statistical analysis. From the results of data processing, it was obtained that partially the two independent variables, namely reward (X1) and punishment (X2) had a positive and significant effect on the work discipline variable (Y), with each value t count > t table (5,468 > 1,692) for the reward variable ( X1) and t count > t table (6.668 > 1.692) for punishment variable (X2), the two independent variables, namely reward (X1) and punishment (X2) were able to influence the dependent variable, namely work discipline (Y) with a value of F count > F table (96.932 > 3.295). R2 test: the coefficient of determination is 0.858 and a positive value, which means, the relationship between reward (X1) and punishment (X2) with work discipline (Y) is 85.80%. This means that the work discipline of employees of PT Fajar Baru Sukses Kabanjahe 85.80% is influenced by reward and punishment and the remaining 14.20% is influenced by other factors not examined in this study.